Government attention allocation in promoting strategic emerging industries in China’s less-developed central region: A policy text analysis of Shanxi province - Xia Li (PLoS ONE, 2026)
Government attention is recognized as a crucial factor in facilitating the sustainable and leapfrog development of strategic emerging industries (SEIs) in less-developed central regions. Focusing on Shanxi province, a typical less-developed central region in China, this study investigates the allocation logic of government attention by analyzing 60 policy documents from 2010 to 2025. Drawing on the attention-based view and policy instrument theory, we establish an Actor-Instrument-Theme framework, and employ a mixed-methods approach combining case study, Latent Dirichlet Allocation (LDA) and Social Network Analysis (SNA). The results reveal weak collaboration among policy actors, an over-reliance on supply-side and environmental policy instruments, and a pyramid-shaped thematic priority structure. This pattern is defined as a foundation-first, gradient-layout approach. While this model may be efficient for early-stage industrial takeoff, it risks long-term distortions such as innovation crowding-out, market entry barriers, and path-dependence lock-in. To promote the sustainable development of SEIs, it is recommended that local governments strengthen policy coordination, optimize policy instrument portfolios, and ensure a balanced deployment of industrial resources.